Corporate Social Responsibility - Consumers' perspective - Mittal, Rahul (2008)
As organizations scale up and stakeholders become increasingly aware of business scenarios, the term corporate social responsibility is more than just a buzzword in business circles. Indeed, to its many advocates, the emergence of corporate social responsibility (CSR) is not only a blueprint for the future, but a new highway to follow for conducting business in an uncertain world that has witnessed the evisceration of many long-accepted norms of conduct (Internal Auditor, 2005).